GASTROINTESTINAL PROBLEMS ASSOCIATED WITH THE EXTENSIVE USE OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS IN CHILDREN - N. I. Ursova (Вопросы современной педиатрии)
The article discusses the mechanisms of action, different effects of non-steroidal anti-inflammatory drugs, an agreed view on the risks of damages to the upper and lower gastrointestinal tract induced by these drugs, as well as ways to eliminate them. The drugs with a relatively small adverse effect on the gastrointestinal tract are described.